ANALISIS KEMAMPUAN SISWA DALAM MENENTUKAN SUBJEK, PREDIKAT, OBJEK, KETERANGAN (SPOK) PADA MATA PELAJARAN BAHASA INDONESIA MATERI CERITA DONGENG DI KELAS 4 SD NEGERI BABADSARI - Ghaniyu Faik Aqshal; Titi Anjarini; Muflikhul Khaq (Cerdas Proklamator, 2023)
Ghaniyu Faik Aqshal "Analysis of Students' Ability in Determining Subjects, Predicates, Objects, Information (SPOK) in Indonesian Language Subjects with Fairy Tale Material in Class 4 of Babadsari State Elementary School". Primary School Teacher Education Thesis, FKIP, Muhammadiyah University Purworejo 2023. This research aims to determine the difficulties and factors of student difficulty in determining Subject, Predicate, Object, Information (SPOK) in Indonesian Language Subjects, Fairy Tale Material in Class 4 of Babadsari State Elementary School. The results of the research were that students had the ability to determine SPOK with five students in the very good category, eight students in the adequate category, and four students in the poor category. Students experience difficulties in determining SPOK as follows; 1. Students have difficulty understanding the meaning of the elements of SPOK; 2. Students have difficulty distinguishing predicate and object elements; 3. Students tend to only master one or two sentence elements. Student difficulty factors are divided into internal and external factors. The internal factors of student difficulties are; 1. Students are not yet fluent in reading; 2. Students are not careful when working on questions. External factors for students to determine SPOK are; 1. Disharmonious family environment; 2. Parents are busy so they lack learning assistance.) Keywords: Ability, SPOK, Tales, Difficulty, Difficulty factors.